2016
DOI: 10.1080/09593330.2016.1156773
|View full text |Cite
|
Sign up to set email alerts
|

Aerobic degradation of ibuprofen in batch and continuous reactors by an indigenous bacterial community

Abstract: Water from six points from the Riachuelo-Matanza basin was analyzed in order to assess ibuprofen biodegradability. In four of them biodegradation of ibuprofen was proved and degrading bacterial communities were isolated. Biodegradation in each point could not be correlated with sewage pollution. The indigenous bacterial community isolated from the point localized in the La Noria Bridge showed the highest degradative capacity and was selected to perform batch and continuous degradation assays. The partial 16S r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(6 citation statements)
references
References 51 publications
0
6
0
Order By: Relevance
“…Ascomycetes (Aspergillus nidulans, Eurotium amstelodami, Bipolaris tetramera), basidiomycetes (Bjerkandera sp., Phanerochaete chrysosporium, Trametes versicolor, Ganoderma lucidum, Irpex lacteus), and individual strains of Gram-negative bacteria (Variovorax sp., Sphingomonas sp.) and Gram-positive bacteria (Bacillus thuringiensis), microbial consortia (active sludge, soil and water consortia) as well as algae (Navicula sp., Chlorella sorokiniana, C. pyrenoidosa) were reported as IBP biodegraders [30,65,[71][72][73][74][75][76][77][78]. In addition, single cases of monocultures of bacteria capable of effective IBP bioconversion have been reported.…”
Section: Plos Onementioning
confidence: 99%
“…Ascomycetes (Aspergillus nidulans, Eurotium amstelodami, Bipolaris tetramera), basidiomycetes (Bjerkandera sp., Phanerochaete chrysosporium, Trametes versicolor, Ganoderma lucidum, Irpex lacteus), and individual strains of Gram-negative bacteria (Variovorax sp., Sphingomonas sp.) and Gram-positive bacteria (Bacillus thuringiensis), microbial consortia (active sludge, soil and water consortia) as well as algae (Navicula sp., Chlorella sorokiniana, C. pyrenoidosa) were reported as IBP biodegraders [30,65,[71][72][73][74][75][76][77][78]. In addition, single cases of monocultures of bacteria capable of effective IBP bioconversion have been reported.…”
Section: Plos Onementioning
confidence: 99%
“…Carballa et al [45] obtained removal percentages of IBU around 40 % using an anaerobic activated sludge system; Nakada et al [46] achieved 90 % of IBU removal during activated sludge treatment; and Langenhoff et al [34] obtained the complete removal of IBU, in 4 days, using activated sludge from a pilot plant treating hospital wastewater. The aerobic degradation of IBU by an indigenous bacterial community was tested by Fortunato et al [47]. These authors found removal percentages around 99 % (33 h, 100 mg L -1 initial concentration), proving the ability of the indigenous communities to improve the treatment of wastewaters containing IBU.…”
Section: Ibuprofen and Paracetamol Removal Performance By Activated Sludge And Comparison With Adsorption Processesmentioning
confidence: 99%
“…> 90%. Fortunato et al [39] performed the biodegradation study of ibuprofen with the indigenous bacterial community.…”
Section: Bacterial Community Associated With Pharmaceuticals Removalmentioning
confidence: 99%